2005
DOI: 10.1001/archinte.165.16.1890
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort Study of Soy Food Consumption and Risk of Bone Fracture Among Postmenopausal Women

Abstract: Soy food consumption may reduce the risk of fracture in postmenopausal women, particularly among those in the early years following menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
2
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(148 citation statements)
references
References 42 publications
4
134
2
8
Order By: Relevance
“…Now a day, soybean is gaining popularity in the food section owing to its functional properties as it is most abundant source of isoflavones (up to 3 mg/g dry weight) in the nature (Dixit et al, 2011). The health benefits associated with soybean consumption are numerous and they are supported by various clinical studies (Setchell and Lydeking-Olsen, 2003;Spence et al, 2005;Messina et al, 2006;Zhang et al, 2005). Its fortification in cereal products is being adopted to complete the amino acid balance and increase the protein quality of the product (Singh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Now a day, soybean is gaining popularity in the food section owing to its functional properties as it is most abundant source of isoflavones (up to 3 mg/g dry weight) in the nature (Dixit et al, 2011). The health benefits associated with soybean consumption are numerous and they are supported by various clinical studies (Setchell and Lydeking-Olsen, 2003;Spence et al, 2005;Messina et al, 2006;Zhang et al, 2005). Its fortification in cereal products is being adopted to complete the amino acid balance and increase the protein quality of the product (Singh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of fracture incidence in the Shanghai cohort (Zhang et al, 2005) and of hip fracture in the Singapore cohort (Koh et al, 2009) shows in both studies one-third reductions in fracture risk when comparing high-with low-soy consumers.…”
Section: Isoflavone and Bone Fracturementioning
confidence: 94%
“…Epidemiological studies suggest that regular consumption of plant-based protein foods reduces one' s risk for chronic diseases such as cancer, heart disease, and stroke. 3,4,5,6 Plant-based foods, such as soy, can provide the body with beneficial agents including vitamins, minerals, fiber, and flavonoids. Numerous clinical trials have investigated the potential of soy to protect against the risk of chronic disease.…”
Section: Soymilkmentioning
confidence: 99%
“…Epidemiological evidence has shown that Asian women, who consume the highest levels of soy protein, have elevated bone mineral density and lower risk of fracture. 1,6 Soy and Diabetes Regular consumption of soy protein may help to reduce symptoms associated with Type 2 Diabetes. Soy has been shown to decrease postprandial hyperglycemia, improve glucose tolerance, and decrease amounts of glycosylated hemoglobin.…”
Section: Soy and Osteoporosismentioning
confidence: 99%